Tổng hợp, xác định cấu trúc phức chất của Ni(II), Pd(II) với 5-bromo-6,7-dihidroxyl-1-metyl-3-sunfoquinolin bằng các phương pháp phổ và tính toán hóa học lượng tử - Hồng Hải, Lê Thị; Anh, Ngô Vân; Ngọc Vinh, Nguyễn Thị; Cường, Ngô Tuấn; Thịnh, Vũ Duy (Vietnam Journal of Chemistry, 2017)
In this research, a new derivative of quinoline, namely 5-bromo-6,7-dihydroxyl-1-methyl-3-sulfoquinole (QOH) as well as two complexes of Ni(II) and Pd(II) with this ligand [M(QOH-1H)2] were synthesized. The molecular formulas and structures of the complexes were determined using a combination of IR, EDX, ESI MS and 1H NMR spectra. Additionally, the structure of the palladium complex was assigned by a combination with quantum chemical calculations using the method of density functional theory which is implemented in Gaussian 09 program package. The results show that this is a square planar complex, in which the QOH ligand coordinates with the center ion Pd(II) via the O atom of its –OH phenol groups and the OH groups have trans configuration. Bond lengths and bond angles around the center metal were determined. Keywords. Pd(II), Ni(II) complexes, derivative of quinoline, structure.